5 - Taxation, Migration and the Creation of a Working Class in Kenya: DOI: 10.4314/ad.v30i4.22242 - Tarus, Isaac (Africa Development, 2005)
Various scholars have questioned the often-stated migrant labour-taxation causal nexus. They have rejected the overworked stereotype that Africans entered la bour service to pay taxes, obtain more livestock and marry more wives. This paper argues that migration was a historical aspect of social change, because migrant labourers made deliberate economic choices on whether to pay taxes either by exploiting available resources or by migrating. Particular analysis is made of the extent to which taxation engendered the creation of a working class cadre. The case of the settler economies of South Africa, Rhodesia, Algeria and Kenya in particular revolved around the transition of the rural population from a pastoral and cultivator economy to a truncated working class in the Thompsonian paradigm. They were not merely, as Atieno-Odhiambo declares, 'cogs in the wheel of capitalism'. Among other reasons, Africans went out in search of paid work for the fact that force was used when their livestock were confiscated unless they left to perform wage labour. Many others went out in search of employment for the independence and self-sufficiency it gave them. The paper argues that a number of young people went out voluntarily to obtain money which they used to pay taxes but also to acquire certain material possessions such as livestock, blankets, clothes and other paraphernalia, and to be come entrepreneurs. As a consequence of all these, we have the emergence of a working class cadre that has become an important life trajectory in Kenya.